Pengaruh Terapi Murrotal terhadap Tingkat Kecemasan pada Lansia dengan Hipertensi di RT 003/007 Sawangan Baru Tahun 2023 - Muhammad Ridat Al Wasiq; Elvie Tresya; Marisca Agustina (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Hypertension is an increase in systolic blood pressure of 140 mmHg and diastolic blood pressure of 90 mmHg. Because hypertension has several factors, one of which is age. Elderly is a phase of declining intellectual and physical abilities. What occurs most often in the elderly is anxiety. Anxiety is an uncomfortable feeling of shame or fear accompanied by a response. Muslims believe in the holy Qur'an as a medicine for heart and physical ailments, the effect of murrotal can reduce anxiety levels. Objective: From this research, to determine the effect of murrotal therapy on anxiety levels in elderly people with hypertension at Rt 003/007 Sawangan Baru in 2023. The population in this study was 36 elderly people, the sample size was 15 respondents. The research design used pre-experimental with a one group pretest-posttest design approach. The data collection method uses the Geriatric Anxiety Scale (GAS) questionnaire to measure anxiety levels. The results showed that the average blood pressure in the elderly before murrotal therapy was 150/100 MmHg, after murrotal therapy it showed 130/90 MmHg, while the level of anxiety in the elderly before and after murrotal Qur'an therapy was an average value. P – value or sig value. (2-tailed) 0.000 which means less than p <0.05 using the Paired Simple T - Test Statistical Test which states that the hypothesis Ha is accepted and Ho is rejected, therefore there is a significant change between before and after the administration of murrotal therapy. So it can be concluded that there is an influence of murrotal therapy on anxiety levels in elderly people with hypertension.